The structure and properties of autogenous laser beam welds in aluminium alloys - Whitaker, Iain Robert (1994)
Autogenous laser beam welds were made in sheets of the aluminium alloys 8090, 8009 and 6061. The Al-Li based alloy 8090 was subjected to both continuous wave CO2 and pulsed Nd:YAG thermal cycles with average powers of 1.5-3.8 kW and 0.8- 0.9 kW respectively. The two techniques were compared for their influence on the 8090 solidified weld pool shape, the fusion zone microstructure and microhardness, the HAZ and the susceptibility of the fusion zone to post-weld heat treatment. It was found that CO2 keyhole welding is preferable to Nd:YAG welding, under the welding conditions investigated, as essential elements such as Li and Mg were lost by evaporation during Nd:YAG processing.